Access to timely cancer treatment initiation in India: extent, determinants and trendsResearch in context - Pritam Halder; Jyoti Dixit; Nidhi Gupta; Nikita Mehra; Ashish Singh; Pankaj Malhotra; Anisha Mathew; Lalit Kumar; Amal Chandra Kataki; Sudeep Gupta; Shankar Prinja (The Lancet Regional Health - Southeast Asia)
Summary: Background: Treatment delays are significantly associated with advanced stage, poor response to treatment, increased mortality risk, poor health outcomes, increased healthcare expenditures among cancer patients. However, factors associated with these delays have not yet been robustly evaluated. In order to bridge this gap, we determined the delayed time to treatment initiation (TTI) among cancer patients in India, ascertained its determinants, and assessed the trends of delayed TTI. Methods: We analysed data collected from 6695 cancer patients seeking outpatient/daycare treatment, recruited at purposively selected seven healthcare facilities across six states of India. Data on socio-demographic and clinical characteristics including date of cancer diagnosis, date of treatment initiation, cancer site, stage and type of treatment were collected to determine the median TTI and ascertain its determinants among cancer patients in India. Time to treatment initiation was calculated as the duration (days) between diagnosis of cancer (histologically/clinically) and date of initiation of treatment. Multi-variable logistic regression was employed to analyse the relationship between the outcome variable (TTI) and each explanatory variable. A Cox Proportional Hazard (CPH) model was used to conduct time-to-event analysis, and to assess the impact of government-funded health insurance on timely cancer treatment initiation. Findings: The median (IQR) overall TTI was 20 (7–39) days, with a mean of 53.7 days (SD, 192.9). The TTI was higher for those having head and neck cancer (median TTI: 29 days, IQR: 10.5–55.5) and those receiving radiotherapy as initial treatment (27.5 days, IQR: 10–49.5). Younger patients, those educated up to graduation level and males had significantly lower odds of delayed TTI. As compared to patients who were diagnosed between 1995 and 2017, those diagnosed after 2018 had a 36% (26–46%) higher odds of timely initiation of treatment within 30 days. Upon stratifying by enrolment under PMJAY, we found that while the access for timely treatment initiation increased by 33% for those who were not enrolled, vs. 90% among those enrolled under PM-JAY. Overall, this shows significant improvement in timely initiation of cancer treatment as a result of introduction of PM-JAY. Interpretation: The study highlights the positive impact of government-funded health insurance schemes on the timely access to cancer treatment in India. Our study recommends expanding AB PM-JAY cancer packages to include cost-effective treatments, increasing population coverage under screening programs and promoting e-RUPI to reduce financial constraints associated with diagnostic services to address delayed treatment initiation due to unknown cancer stages. Funding: Department of Health Research, Ministry of Health and Family Welfare, New Delhi, India.